Customer Satisfaction, Product Quality and Performance of Companies - Petr Suchánek; Jiří Richter; Maria Králová (Review of Economic Perspectives, 2015)
This paper presents an analysis of quality, customer satisfaction and business performance in food industry. The main objective of the research is to determine the influence of quality on customer satisfaction and on business performance and competitiveness. In particular, this paper answers the following research question: Does the quality of a product result in a satisfied customer and thereby in a well-performing business? Customer satisfaction is defined as the satisfaction of the customer with a product and the business performance as a capability to generate profit. Therefore, satisfaction was examined by the means of a survey using questionnaires, and the performance was measured by financial data. We managed to find a correlation between the main factors, although partial results were due more factors mostly statistically insignificant.
Keywords: 330